Optimalisasi Pembelajaran Literasi Numerasi Melalui Pelatihan Penggunaan Website Google Sites bagi Guru Komunitas Belajar - Nurul Renaningtias; Atika Susanti; Bagus Mirzana; Cahyo Prasetyo; Dwi Lestari (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
The main goal of this community service activity is to enhance teachers' numeracy literacy skills through the use of Google Sites. The partner for this service activity is SDN 8 Bengkulu Tengah, Desa Rindu Hati. The method used for this community service includes the IPPE method, which comprises: (1) Needs Identification, (2) Planning, (3) Training Implementation, and (4) Evaluation. The evaluation instrument used was a test sheet. Based on the assessment results, there was a significant improvement in teachers' skills, with the average pretest score rising from 51.57 to 85.56 in the posttest. The N-Gain score averaged 0.74, which falls into the